Evaluation of antioxidant, heavy metal analysis, brine-shrimp toxicity test and phytochemical analysis of Fagraea acuminatissima Merr. (Loganiaceae) stem extracts - Tang, Bee Eik (2021)
Fagraea acuminatissima Merr. (Loganiaceae) is a medicinal herb consumed by local people as a tonic. However, there is a lack of information on the scientific study of this plant. Hence, the aims of this study were to determine the antioxidant activities, toxicity and phytochemical data of F. acuminatissima stem extracts. In this study, F. acuminatissima stems were extracted with two solvents: methanol and water. Methanol extract was dried using rotary evaporator to produce Methanol Extract (ME), and the water extracts were then further dried by using freeze dryer and spray dryer, producing Freeze-dried Water Extract (FDWE) and Spray-dried Water Extract (SDWE), respectively. The antioxidant activities of all extracts were determined through three assays: DPPH, ABTS and FRAP. Firstly, for DPPH free radical scavenging assay, ME showed the highest scavenging activity with the IC50 value of 67.00 ± 1.00 μg/ml, followed by SDWE (86.47 ± 0.87 μg/ml) and FDWE (122.17 ± 0.76 μg/ml). Meanwhile, in ABTS assay, ME showed the lowest IC50 of 77.40 ± 0.72 μg/ml, followed by SDWE (101.83 ± 0.35 μg/ml) and FDWE (121.73 ± 1.05 μg/ml). On the other hand, FRAP assay for ME, SDWE and FDWE were 0.956 ± 0.066 TE g/g, 0.662 ± 0.075 TE g/g and 0.407 ± 0.049 TE g/g, respectively. The result showed that ME had the greatest antioxidant activities followed by SDWE and FDWE. For Folin-Ciocalteau method, ME contained the highest amount of total phenolic contents (TPC) (0.622 ± 0.054 GAE g/g extract), followed by SDWE (0.423 ± 0.092 GAE g/g extract) and FDWE (0.268 ± 0.047 GAE g/g extract), meanwhile, for aluminium chloride colorimetric method, the flavonoid contents (TFC) were found highest in ME (0.919 ± 0.073 QE g/g extract), followed by SDWE (0.567 ± 0.091 QE g/g extract) and FDWE (0.128 ± 0.011 QE g/g extract). Statistical analysis showed that there was positive correlation between antioxidant activity and TPC and TFC of the extracts. Toxicity of the F. acuminatissima stem extracts was determined by using Brine Shrimp Lethality Test (BSLT). Result showed that the LC50 of all extracts might be above 1000 ug/ml, which indicated that the extracts were not toxic. Furthermore, the content of heavy metal in stem of F. acuminatissima was determined by using Atomic Absorption Spectroscopy (AAS). Result showed in the stem, in ascending order of heavy metal concentration is as follows: Cr > Hg > Cd > As > Pb > Ni > Co. The concentration of As, Cr, Pb, Hg and Ni found in the stem of F. acuminatissima was within the permissible limit, whereas the concentration of Cd and Co found in the stem was higher than the approved daily consumption limit. TLC analysis (silica F254) for ME, FDWE and SDWE showed the presence of 12 spots (Rf:0.03-0.67), 7 spots (Rf: 0.02-0.63) and 10 spots (Rf: 0.02-0.67), respectively. For High Performance Liquid Chromatography (HPLC), ME showed highest value of components (11 peaks), followed by SDWE (6 peaks) and FDWE (5 peaks). Peaks spectrum analyses at 200-800 nm showed the presence of phenolic compound (probably flavonoid). Overall, the study of the F. acuminatissima stem extracts showed the presence of antioxidant potentials which may be due to the presence of secondary metabolites from phenolic compound. The toxicity studies also indicated that the plant is non-toxic and is safe to be used as traditional medicine.